Pharmacokinetics, safety and efficacy of a recombinant factor IX product, trenonacog alfa in previously treated haemophilia B patients - Collins, P. W.; Quon, D. V. K.; Makris, M.; Chowdary, P.; Kempton, C. L.; Apte, S. J.; Ramanan, M. V.; Hay, C. R. M.; Drobic, B.; Hua, Y.; Babinchak, T. J.; Gomperts, E. D. (Haemophilia : the official journal of the World Federation of Hemophilia, 2018)
Introduction Trenonacog alfa (IB1001) is a recombinant factor IX (rFIX) manufactured in Chinese hamster ovary (CHO) cells. IB1001 was evaluated in a multicentre clinical trial with haemophilia B patients. Aim The aim was to establish IB1001 pharmacokinetic non‐inferiority to comparator rFIX, safety and efficacy in previously treated patients (PTPs) with haemophilia B. Methods Subjects were severe or moderately severe haemophilia B adult and adolescent PTPs with no history of FIX inhibitors. Results IB1001 PK non‐inferiority to comparator rFIX was demonstrated through ratio of AUC0‐∞ in 32 subjects. IB1001 was well tolerated in all 76 treated subjects; the most common adverse drug reaction was headache (2.6% of subjects) and there were no reports of FIX inhibitors. Transient non‐inhibitory binding FIX antibodies and anti‐CHO cell protein antibodies developed in 21% and 29% of subjects respectively; no safety concerns were associated with development of these antibodies. Prophylaxis (mean duration ± SD: 17.9 ± 9.6 months, mean dose: 55.5 ± 12.9 IU/kg, median 1.0 infusion per week) was effective in preventing bleeds (median annual bleed rate: 1.52, interquartile range: 0.0‐3.46). One or two IB1001 infusions resolved 84% of the bleeds, while for 84% of treatments haemostatic efficacy of IB1001 was rated excellent or good. IB1001 haemostatic efficacy for all 19 major surgeries was rated adequate or better than adequate. Conclusions IB1001 is safe and efficacious for treatment of bleeds, routine prophylaxis and perioperative management in haemophilia B patients.